1999
DOI: 10.1103/physreve.60.48
|View full text |Cite
|
Sign up to set email alerts
|

Fisher-based thermodynamics: Its Legendre transform and concavity properties

Abstract: It is shown that the Legendre-transform structure of thermodynamics can be replicated without any change if one replaces the entropy S by Fisher's information measure I. Also, the important thermodynamic property of concavity is shown to be obeyed by I. By this use of the Fisher information measure we develop a thermodynamics that seems to be able to treat equilibrium and nonequilibrium situations in a manner entirely similar to the conventional one.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
164
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 103 publications
(169 citation statements)
references
References 22 publications
5
164
0
Order By: Relevance
“…and, as stated above, recognize that T dI plays the role of a heat-change dQ F , as expected (but not explicitly discussed there) from the philosophy espoused in [8]. Thus, we have here shown that work is represented by changes in expectation values.…”
Section: A Relation For the Differential Of Fisher's Measurementioning
confidence: 66%
See 4 more Smart Citations
“…and, as stated above, recognize that T dI plays the role of a heat-change dQ F , as expected (but not explicitly discussed there) from the philosophy espoused in [8]. Thus, we have here shown that work is represented by changes in expectation values.…”
Section: A Relation For the Differential Of Fisher's Measurementioning
confidence: 66%
“…[8]. It was shown there that, if we are discussing a thermodynamical setting involving M extensive variables O i , we can recover the formal, Legendre-structure of thermodynamics if we minimize the Fisher information measure I subject to appropriate constraints.…”
Section: A Relation For the Differential Of Fisher's Measurementioning
confidence: 99%
See 3 more Smart Citations